The Search for New Odorants: Synthesis of Animalic Fragrant and Musky/Ambery Compounds. Issue 10 (October 2014) - Plessis, Caroline
Abstract An overview of the recent research which allowed us to discover novel animalic odorants is presented. The new derivatives were prepared from readily available starting materials via easy reaction steps in good yields. They possess very different structures, such as bicyclic pentanols, glycolates, or tricyclic ketones, and all show interesting notes in the animalic fragrant family: from costus, leathery to ambery and musky scents, making them all attractive for different purposes.